Gambaran Implementasi Standar Promosi Kesehatan Rumah Sakit (PKRS) di RSUD Ibnu Sina Kabupaten Gresik - Diana fairuz; Katmini Katmini (Universitas Ivet, 2022)
Every hospital is required to implement PKRS (Hospital Health Promotion). PKRS implementation includes implementation of PKRS management and fulfillment of PKRS standards. Based on a preliminary study conducted by researchers at Ibnu Sina Hospital, it was stated that the implementation of PKRS was still not optimal according to Permenkes No. 44 of 2018 concerning PKRS. This research is qualitative research with descriptive approach the aim of describing the implementation of PKRS standards based on Permenkes No.44 of 2018. Data collection was used by in-depth interviews, observation, review of research supporting documents. Data analysis was performed using concept of source triangulation. Interviews were conducted 12 respondents, consisting of sructural and functional officers. The results showed that the implementation of PKRS at Ibnu Sina Hospital was not optimal according to PKRS standards, including the organizational was still in the form of a unit, an assessment of hospital human resources had not been carried out and there was no research on PKRS. The conclusion is hoped that the Hospital will support factors related to improving the organizational form of the Marketing Unit and PKRS become Installations, form special team to carryout Hospital HR assessments and encourage Hospital HR to conduct research on PKRS